2014
DOI: 10.4278/ajhp.110516-qual-200
|View full text |Cite
|
Sign up to set email alerts
|

Social Entrepreneurship in Religious Congregations' Efforts to Address Health Needs

Abstract: Purpose Examine how religious congregations engage in social entrepreneurship as they strive to meet health-related needs in their communities. Design Multiple case studies. Setting Los Angeles County, California. Participants Purposive sample of 14 congregations representing diverse races-ethnicities (African American, Latino, and white) and faith traditions (Jewish and various Christian). Method Congregations were recruited based on screening data and consultation of a community advisory board. In ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Further, our previous in-depth, qualitative research has found that most congregational HIV activities are conducted in partnership with external organizations 9,46 and that congregations may be better suited as collaborators rather than the primary infrastructure for ongoing service provision. 47 Additionally, our data are cross-sectional; thus, we can draw no conclusions regarding causality. Important variables were omitted, such as clergy education level, which was shown to be important in previous analyses of the 1998 NCS, 28 but which was not measured in the 2006-2007 wave.…”
Section: Limitationsmentioning
confidence: 93%
“…Further, our previous in-depth, qualitative research has found that most congregational HIV activities are conducted in partnership with external organizations 9,46 and that congregations may be better suited as collaborators rather than the primary infrastructure for ongoing service provision. 47 Additionally, our data are cross-sectional; thus, we can draw no conclusions regarding causality. Important variables were omitted, such as clergy education level, which was shown to be important in previous analyses of the 1998 NCS, 28 but which was not measured in the 2006-2007 wave.…”
Section: Limitationsmentioning
confidence: 93%
“…With 80% of the U.S. population having a religious affiliation, clergy have a unique opportunity to create awareness and open conversations about domestic violence (Nordtvedt & Chapman, 2011). As a trusted and social community, congregations have the opportunity to provide an environment of support for victims of domestic violence (Werber et al, 2014). Findings from this 10-year study indicate that both congregational members and clergy want to create an environment of support and help for victims of domestic violence.…”
Section: Resultsmentioning
confidence: 99%
“…In many cases, a church setting may be the only source of social support that a victim of domestic violence may encounter (Barnett, 2001). Perceived social support is exceptionally important for victims, and religious congregations have the capacity to be both trusted and social (Hansen, Eriksen, & Elklit, 2014; Werber, Mendel, & Derose, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, a church setting may be the only source of social support that a victim of domestic violence may encounter (Barnett, 2001). Perceived social support is exceptionally important for victims, and religious congregations have the capacity to be both trusted and social (Hansen et al, 2014; Werber et al, 2014).…”
Section: Introductionmentioning
confidence: 99%